The effect of working capital management and capital structure on firm value through profitability as a mediating variable in manufacturing companies during the COVID-19 pandemic - Sari, Dinda Puspita; Sari, Prima Yusi; Cempaka, Adisti Gilang (Journal of Accounting Auditing and Business, 2025)
During the COVID-19 pandemic, many companies experienced a decline in performance due to market uncertainty, cash flow limitations, and disruptions to supply chains. Therefore, effective capital management to support company performance became crucial. This study aims to analyze the impact of working capital management (CCC) and capital structure (DER) on firm value (Tobin’s Q) through profitability (ROA) among manufacturing companies listed on the Indonesia Stock Exchange during the Covid-19 pandemic from 2020 to 2022. The sample was selected using purposive sampling, resulting in a total of 118 companies. Data analysis includes descriptive statistics, normality tests, Robust Least Squares regression, coefficient of determination tests, partial tests, path analysis, and Sobel test. The results indicate that the independent variables CCC and DER do not have a direct significant effect on firm value during the Covid-19 pandemic. However, when profitability (ROA) is considered as a mediating variable, both CCC and DER show a negative impact on firm value. Furthermore, the study reveals a differing direct relationship between capital structure (DER) and firm value, where the relationship is positive.